2022
DOI: 10.3390/children9121921
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 Phases Have Impacted Psychiatric Risk: A Retrospective Study in an Emergency Care Unit for Adolescents

Abstract: Dramatic events during the COVID-19 pandemic have acutely impacted the psychosocial environment worldwide, with negative implications for mental health, particularly for more vulnerable children and adolescents with severe psychiatric illnesses. Some data suggest that the pandemic waves may have produced different psychopathological consequences, further worsening in the second phase of the pandemic, compared to those in the first lockdown, soon after March 2020. To test the hypothesis of a further worsening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Concerning self-injurious behaviors among the admitted patients during the quarantine periods, an increased frequency of non-suicidal self-injurious behaviors was observed compared to the reference periods (i.e., 58.6% during the quarantine periods vs. 43.2% during the reference periods). This finding aligns with the results of previous studies of adolescents during COVID-19 [16,[31][32][33]. As proposed by Plener [30], non-suicidal self-injurious behaviors are often applied as an emotion regulation strategy to temporarily decrease or eliminate negative emotions.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning self-injurious behaviors among the admitted patients during the quarantine periods, an increased frequency of non-suicidal self-injurious behaviors was observed compared to the reference periods (i.e., 58.6% during the quarantine periods vs. 43.2% during the reference periods). This finding aligns with the results of previous studies of adolescents during COVID-19 [16,[31][32][33]. As proposed by Plener [30], non-suicidal self-injurious behaviors are often applied as an emotion regulation strategy to temporarily decrease or eliminate negative emotions.…”
Section: Discussionsupporting
confidence: 91%
“…One example is the COVID-19 pandemic, which has affected the psychosocial environment of vulnerable children and adolescents by causing loss of lives, isolation, contact restrictions, and disruption of daily rhythms, particularly eating and sleeping routines. In this regard, Mucci and colleagues [ 30 ] and Beghi and colleagues [ 31 ] found that non-suicidal self-injury significantly increased among Italians during the lockdown periods in 2020 and 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of self-harm and risky behavior is increasing and becoming more evident, as seen in Ougrin and colleagues’ investigation [ 41 ] of self-harm in adolescents in 10 countries, including Italy. They found that the proportion of teens turning to inpatient emergency departments increased by 50% in 2019 and 57% in 2020, with an increase in those having difficulty with emotion regulation between 58% and 66% likely due to the COVID-19 pandemic in the past two years [ 30 ]. These data highlight the importance of investigating these behaviors with culturally appropriate measures [ 42 , 43 ], which are useful in each specific social context, taking into account social and moral norms.…”
Section: Introductionmentioning
confidence: 99%
“…Economic uncertainty among families with a lower socio-economic status, alteration of sleep habits with inversion of the circadian rhythms, decreased physical activity, unhealthy eating habits, and possible difficulties in family relationships including exposure to intrafamilial violence/traumas are all possible reasons for the adverse health outcomes relating to the pandemic lockdown [24]. Several other studies reported an increase in ED psychiatric consultations from suicide attempts after the spring season of 2020, and adolescents have been reported as the most vulnerable group [21,[25][26][27][28]. The present study showing an increase in CP consultations for suicidal ideation and attempts confirms the results of a previous Italian study, providing information on the persistence of this increase during the year after gradual resumption of normal activities for both adults and juveniles.…”
Section: Discussionmentioning
confidence: 99%